Intracellular behavior of Nocardia seriolae and its apoptotic effect on RAW264.7 macrophages - Liu, Wenwen; Deng, Yuting; Tan, Aiping; Zhao, Fei; Chang, Ouqing; Wang, Fang; Lai, Yingtiao; Huang, Zhibin (Frontiers in Cellular and Infection Microbiology, 2023)
Nocardia seriolae, an intracellular gram-positive pathogen, is prone to infect immunocompromised and surface-damaged fish, causing serious losses to the aquaculture industry. Although a previous study demonstrated that N. seriolae infects macrophages, the persistence of this bacterium in macrophages has not been well characterized. To address this gap, we used the macrophage cell line RAW264.7, to investigate the interactions between N. seriolae and macrophages and deciphered the intracellular survival mechanism of N. seriolae. Confocal and light microscopy revealed that N. seriolae entered macrophages 2 hours post-inoculation (hpi), were phagocytosed by macrophages at 4–8 hpi, and induced the formation of multinucleated macrophages by severe fusion at 12 hpi. Flow cytometry, evaluation of mitochondrial membrane potential and release of lactate dehydrogenase, and observation of the ultrastructure of macrophages revealed that apoptosis was induced in the early infection stage and inhibited in the middle and later periods of infection. Additionally, the expression of Bcl-2, Bax, Cyto-C, Caspase-3, Capase-8, and Caspase-9 was induced at 4 hpi and then decreased at 6–8 hpi, illustrating that N. seriolae infection induces the activation of extrinsic and intrinsic apoptotic pathways in macrophages, followed by the inhibition of apoptosis to survive inside the cells. Furthermore, N. seriolae inhibits the production of reactive oxygen species and releases large amounts of nitric oxide to persist in macrophages during infection. The present study provides the first comprehensive insight into the intracellular behavior of N. seriolae and its apoptotic effect on macrophages, and may be important for understanding the pathogenicity of fish nocardiosis.